Mobile Robotics 2009
DOI: 10.1142/9789814291279_0091
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Dog Motion Measurements to Support a Simple Model of Rotary Galloping Locomotion

Abstract: The gallop is the preferred gait by mammals for agile traversal through terrain. This motion is intrinsically complex as the feet are used individually and asymmetrically. Experimental data for the gallop are limited due the large workspace needed because of the gait's speed and long traversal. A generalized motion measurement strategy is adopted based on high-speed, motion capture with a reduced marker set and an emphasis on body and leg kinematics and with limited ground reaction force measurement. This allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…In one study [10], researchers fitted dogs' hind limbs with motion capture markers, and quantitatively diagnosed abnormal gaits. In another research project [11], caninegalloping locomotion, which cannot easily be observed because of spatial restrictions, was quantitatively evaluated using a motion capture system. In this study, researchers propose a measurement system based on a layout of motion capture markers.…”
Section: Previous Studies Conducting Quantitative Evaluations Of Dog mentioning
confidence: 99%
“…In one study [10], researchers fitted dogs' hind limbs with motion capture markers, and quantitatively diagnosed abnormal gaits. In another research project [11], caninegalloping locomotion, which cannot easily be observed because of spatial restrictions, was quantitatively evaluated using a motion capture system. In this study, researchers propose a measurement system based on a layout of motion capture markers.…”
Section: Previous Studies Conducting Quantitative Evaluations Of Dog mentioning
confidence: 99%